Basics design 02 : layout - Ambrose, Gavin; Harris, Paul. (New York: AVA Publishing, 2005)
Addresses the practical and aesthetic considerations of layout such as where and how the content will be viewed, whether the format is a magazine, website, television graphic or bottle of bubble bath. This book will prove indispensable to anyone wishing to acquire a thorough knowledge of the principles of layout as used in modern design. Through the considered application of these principles a more balanced and effective design can be achieved.
Keywords: Elements